Menyoal Pasal 44 Ayat (4) UU PKDRT: Antara Perlindungan Atau Normalisasi Kekerasan Ringan Dalam Rumah Tangga - Hamit Tantio Lumban Gaol; Theo Octapianus Siahaan (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
This article examines the legal and sociological issues surrounding Article 44 paragraph (4) of Indonesia’s Domestic Violence Elimination Act (Undang-Undang Penghapusan Kekerasan Dalam Rumah Tangga/PKDRT), which is considered problematic for potentially normalizing acts of minor domestic violence. Although the PKDRT was enacted with the fundamental objective of providing protection for women and children as vulnerable groups, the formulation of Article 44(4) introduces relatively lenient sanctions and adopts a complaint-based (delik aduan) mechanism. These characteristics significantly weaken legal protection for victims and may create space for perpetrators to evade accountability. Furthermore, the absence of clear legal parameters regarding the concept of “minor violence” leads to subjective interpretation by law enforcement officials, resulting in inconsistent application of the law and undermining the realization of substantive justice. Using normative juridical and sociological approaches, this article analyzes how the provision contradicts the spirit and objectives of the PKDRT as a preventive and protective legal instrument. The study emphasizes the urgency of reformulating Article 44 paragraph (4) to eliminate ambiguity, strengthen victim protection, and ensure legal certainty. Ultimately, such reform is essential to uphold the principles of justice, humanity, gender equality, and the original purpose of the PKDRT in combating domestic violence effectively